2006
DOI: 10.1007/s00418-006-0183-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-apoptotic programmed cell death induced by a copper(II) complex in human fibrosarcoma cells

Abstract: A0, a Cu(II) thioxotriazole complex, produces severe cytotoxic effects on HT1080 human fibrosarcoma cells with a potency comparable to that exhibited by cisplatin. A0 induced a characteristic series of changes, hallmarked by the formation of eosin- and Sudan Black-B-negative vacuoles. No evidence of nuclear fragmentation or caspase-3 activation was detected in cells treated with A0 which, rather, inhibited cisplatin-stimulated caspase-3 activity. Membrane functional integrity, assessed with calcein and propidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 39 publications
5
50
0
Order By: Relevance
“…To assess the involvement of caspases in the A0-induced cell death, we used specific inhibitors of caspase-3 as well as of other caspases. Consistently with our previous results (18), the cytotoxic effect of A0 was not affected by any of the caspase inhibitors tested (Fig. 1b), whereas the cisplatin-induced decrease of viability was significantly decreased.…”
Section: Differential Sensitivities Of Human Cancer Cells To A0 Andsupporting
confidence: 93%
See 4 more Smart Citations
“…To assess the involvement of caspases in the A0-induced cell death, we used specific inhibitors of caspase-3 as well as of other caspases. Consistently with our previous results (18), the cytotoxic effect of A0 was not affected by any of the caspase inhibitors tested (Fig. 1b), whereas the cisplatin-induced decrease of viability was significantly decreased.…”
Section: Differential Sensitivities Of Human Cancer Cells To A0 Andsupporting
confidence: 93%
“…Cisplatin-Previous results from our laboratory have demonstrated that the copper(II) complex A0 causes non-apoptotic death of cancer cells (18). As shown in Fig.…”
Section: Differential Sensitivities Of Human Cancer Cells To A0 Andmentioning
confidence: 94%
See 3 more Smart Citations